2018
DOI: 10.3390/foods7020021
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Chemical Profiles, Antioxidant and Antimicrobial Activities of Commercial Vegetable Edible Oils Marketed in Japan

Abstract: This study analyzed chemical components and investigated the antioxidant and antimicrobial activities of fourteen vegetable edible oils marketed in Japan. High-performance liquid chromatography (HPLC) was used to identify and quantify principal phenolic acids and flavonoids. In the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, sunflower, safflower, canola, soybean, Inca inchi, sesame, and rice bran showed markedly greater activity, whilst the percentage of lipid peroxidation inhibition (LPI%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 34 publications
3
42
0
2
Order By: Relevance
“…The results showed a high antioxidant activity for all accessions, which ranged from 20.6% to 68.9% (Table 4). This activity has been described by several works [5,19,20]. Shirvani et al [21] reported that this activity had a rate of 50% at the beginning of safflower seed germination.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The results showed a high antioxidant activity for all accessions, which ranged from 20.6% to 68.9% (Table 4). This activity has been described by several works [5,19,20]. Shirvani et al [21] reported that this activity had a rate of 50% at the beginning of safflower seed germination.…”
Section: Discussionsupporting
confidence: 53%
“…Koyama et al [3] confirmed the effects of safflower seed extract and its phenolic constituents on atherosclerosis. Several studies have been carried out to evaluate the phenolic compounds and antioxidant activity of Asteraceae seeds including safflower [4,5], sunflower [6], and artichoke [7]. Moreover, recent research has reported that the root of Carthamus caeruleus L. growing wild in Mediterranean regions and especially in Algeria has a potent antioxidant activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that the antioxidant activity of chia oil is much lower than chia seeds although it was not proportional to the decrease of the TPC, suggesting that other compounds not detected using these analytical conditions could be responsible [ 60 ]. The results reported by Xun et al [ 77 ] seem to confirm this, because the DPPH scavenging activity reported for different edible oils was not totally related with the TPC; in the case of chia oil the DPPH value was the lowest, together with avocado oil. In reference to that, Itxaina et al [ 45 ] reported that the high level of polyunsaturated fatty acids (PUFAs) would be the main cause for the low oxidative stability prevailing over the antioxidant effects associated with bioactive components (tocopherols, polyphenols, carotenoids, and phospholipids) present in chia seed oils.…”
Section: Antioxidant Activity In Chia Quinoa and Their Coproductmentioning
confidence: 87%
“…The β-carotene bleaching assay was performed as described by Xuan et al [32] with some modifications. An amount of 2 mg of β-carotene/linoleic acid was initially prepared by dissolving in 10 mL of chloroform.…”
Section: Determination Of Antioxidant Activity With the β-Carotene Blmentioning
confidence: 99%